Analysis Of Illocutionary Acts in Dedi Mulyadi’s Speech at The National Awakening Ceremony: Let the Sarcastic People Be Hurt Forever - Eisya Dalila Nasution (Indonesian Journal of ELT and Applied Linguistics, 2024)
This study examines the illocutionary acts in Dedi Mulyadi’s speech delivered during the National Awakening Ceremony, utilizing Searle’s (1976) taxonomy within a descriptive qualitative framework. A total of 72 utterances were identified and categorized: 40 assertive (55.5%), 15 directive (20.8%), 10 commissive (13.9%), 5 expressive (6.9%), and 2 declarative (2.8%) acts. Assertives dominate, reflecting Dedi’s sarcastic and informational style, while the rarity of declaratives underscores his emphasis on persuasion rather than formal proclamation. The analysis reveals how Dedi strategically employs sarcasm and militaristic directives to assert authority, critique societal issues, and influence public perception. These rhetorical choices strengthen his image as a decisive leader but may limit dialogic engagement. The study highlights the communicative function of illocutionary acts in political discourse and contributes to a deeper understanding of how language performs social and political actions in contemporary Indonesian rhetoric.